The Influence Of Service Quality, Product Quality And Social Media Marketing On Sound System Customer Satisfaction : (AR Pro Nganjuk Case Study) - Fadila, Sanggita Nur; Zulistiani, Zulistiani (Universitas Nusantara PGRI Kediri, 2024)
Research objectives: The objective of this research is to ascertain and analyze the significant influence of service quality, product quality, and social media marketing on customer satisfaction with the AR Pro Nganjuk sound system partially and simultaneously. Design/Method/Approach: This research is a type of quantitative research with a causality approach. The population of this study was all customers in the AR Pro Nganjuk sound system, this research instrument used a questionnaire involving 40 customer respondents in the AR Pro Nganjuk sound system. The sampling technique uses nonprobability sampling (incidental sampling), and the data analysis technique uses multiple linear regression tests. Data processing is carried out using SPSS 23. Research Findings:The findings of this research demonstrate that service quality, product quality, and social media marketing collectively and individually influence customer satisfaction to a noteworthy degree in the AR Pro Nganjuk sound system. Theoretical Contribution: This research contributes to the understanding and provides insight related to improving the quality of products, services, and social media marketing in order to achieve success in the market. Policy Implications: For companies, this research can be an overview in the company's quality improvement strategy. So as to minimize the risks that may occur. Research Limitations: This study focuses on service quality, product quality and Social Media Marketing as independent variables, as well as customer satisfaction as the dependent variable. This research was conducted on customers who purchased Nganjuk's AR Pro Sound System product directly.